1855-56 Tenn. Acts 92, ch. 81, § 2 - (:unkn) unknown (General Publisher, 1856)
Prohibited the sale or transfer of any pistol, Bowie knife, dirk, Arkansas toothpick, or hunter’s knife to a minor. Excepted the transfer of a gun for hunting.
--
Keywords: TRANSFER - MINORS